Disputas familiares por los cacicazgos en la Audiencia de Quito durante el siglo XVIII - Daza Tobasura, Paula (Universidad Santiago de Cali, 2020)
This chapter explores how indigenous women used legal strategies to get appointments as cacicas in the Court on the Audiencia of Quito, during the second half of the 18th century. Despite the fact that the position of chieftain was preserved for men, women used the judicial apparatus to their advantage to claim a family right that could be taken by a female.